2021
DOI: 10.2967/jnumed.120.249300
|View full text |Cite
|
Sign up to set email alerts
|

Utility of 211At-Trastuzumab for the Treatment of Metastatic Gastric Cancer in the Liver: Evaluation of a Preclinical α-Radioimmunotherapy Approach in a Clinically Relevant Mouse Model

Abstract: A liver metastasis from a primary gastric cancer (LMGC) is relatively common and results in an extremely poor prognosis due to a lack of effective therapeutics. We here demonstrate in a clinically-relevant mouse model that an α-radioimmunotherapy (α-RIT) approach with astatine-211-labeled-trastuzumab ( 211 At-trastuzumab) has efficacy against LMGCs that are positive for human epidermal growth factor receptor 2 (HER2). Methods: 211 At was produced in a cyclotron via a 209 Bi (α, 2n) 211 At reaction. 211 Attra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…To take advantage of this new treatment, the use of astatine in radiotherapy research has been gaining in recent years. Astatine has a shorter half-life than other α particle emitters which makes it less likely to stay active for long periods of time in the patient's body, but not so short that it is not logistically viable to be used [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…To take advantage of this new treatment, the use of astatine in radiotherapy research has been gaining in recent years. Astatine has a shorter half-life than other α particle emitters which makes it less likely to stay active for long periods of time in the patient's body, but not so short that it is not logistically viable to be used [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the cytotoxicity of iso-211 At-SAGMB-5F7 (D 0 5 1.313 kBq/mL) was higher than that determined for 211 At-trastuzumab (1.7 kBq/mL) under similar conditions on the same BT474 cell line (28). Therapeutic responses after 211 At-trasuzumab treatment have been observed in various animal models; however, except for a recent study (33), these have involved direct delivery into a tumor-compromised compartment (6,34). After intrathecal delivery, regional differences in therapeutic effectiveness against carcinomatous meningitis were observed with 211 At-trasuzumab, suggesting that inhomogeneous distribution of the labeled mAb had occurred (6).…”
Section: Discussionmentioning
confidence: 85%
“…The biological effect of 211 At‐trastuzumab was twice as great as that of external radiation therapy [41], and 211 At‐trastuzumab inhibited the growth of HER2‐positive tumor cells. Another study showed that 211 At‐trastuzumab extended median survival without posing a severe risk of harm in the treatment of liver metastases from primary gastric cancer [62].…”
Section: Preclinical Studiesmentioning
confidence: 99%